Análise comparativa dos custos operacionais e de implementação de sistemas de abastecimento de água considerando reservatório elevado e booster - Cremasco, João Pedro (Universidade Federal de São Carlos, 2022)
Water supply systems in their reservoir and distribution stage can present different solutions, such as elevated reservoirs or booster pressurization systems. The elevated reservoirs are composed of an upper and lower chamber, with the water being pumped from the lower to the upper chamber, from which it is distributed by gravity. The pressurization systems are composed of a supported reservoir and a variable speed pump, which works uninterruptedly unlike the elevated reservoir configuration. The present work sought, by means of a hydraulic modeling in EPANET, to make a comparison of operational costs and implantation costs of these two reservoir and distribution configurations, having as study object the lot "Jardim do Bosque" located in the city of São Carlos (SP). The variables analyzed were the volume stored in each one of the reservoir chambers, as well as the pumped flow rate in each one of the situations. The results obtained indicate that the elevated reservoir has lower energy operational costs and the pressurizing system has lower reservoir implementation costs. For the case studied, the best alternative is the elevated reservoir, due to the considerations made about the beneficiaries.
Comparative analysis of operational and implementation costs of water supply systems considering high reservoir and booster
Keywords: Abastecimento de água; Reservação; Custo; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO